Southern blue criminology: rethinking ocean harmscapes in a global context - Hübschle, Annette; Berg, Julie (Frontiers in Conservation Science, 2024)
This paper introduces southern blue criminology, a novel theoretical framework that extends traditional criminological analysis to encompass the environmental harms affecting the world's oceans, particularly from a Global South perspective. This approach critiques crime-centric analysis and expands upon the concept of "harmscapes"—areas significantly impacted by ecological damage—by integrating socio-economic and cultural contexts often overlooked by prevailing enforcement paradigms developed in the Global North. Through a critical review of existing criminological theories and maritime enforcement practices, this study highlights the inadequacies of current approaches that fail to account for the transnational and complex nature of oceanic harms. Southern blue criminology is proposed through four integrative perspectives: shifting from a crime-centric view to embracing a broader conception of ocean harmscapes; moving beyond state-centric responses to foster whole-of-society involvement including non-state actors; transcending Western-centric governance models in favor of context-dependent strategies that respect local knowledge and practices; and expanding the analytical frame from human-centric approaches to include human-nonhuman assemblages, recognizing the ocean as an active participant in ecological and social interactions. The framework aims to foster more effective and sustainable management of marine environments, proposing a shift from a punitive focus to a more comprehensive, preventive, and restorative approach. The implications of this research are significant, suggesting a transformative shift in policies to better address the intricate web of factors contributing to maritime environmental crimes and to enhance global ecological justice.